Ableism in Academia. Theorising experiences of disabilities and chronic illnesses in higher education - Hewlett, Sally-Jayne (Critical Studies in Teaching and Learning, 2023)
Brown, N., & Leigh, J. (eds) 2020. Ableism in Academia. Theorising experiences of disabilities and chronic illnesses in higher education. London: UCL Press.